Design and evaluation of taste masked chewable dispersible tablet of lamotrigine by melt granulation - Pankaj P. Amrutkar; Sanjay B. Patil; Abhijeet N. Todarwal; Manoj A. Wagh; Parag D. Kothawade; Rajendra K. Surawase (International Journal of Drug Delivery, 2010)
Lamotrigine, an antiepileptic drug (AED) of the phenyltriazine class, is chemically unrelated to existing antiepileptic drugs. Lamotrigine is also used in the treatment of depression and bipolar disorder. But it is a bitter drug and slightly soluble in water. Thus, in the work under taken, an attempt was made to mask the taste and to formulate into a chewable dispersible tablet by complexation with Precirol ATO-05, which also acts as taste masking agent. Since, these tablets can be swallowed in the form of dispersion; it is suitable dosage form for paediatric and geriatric patients. Drug-Precirol ATO-05 was prepared in drug to Precirol ATO-05 ratio of 1:2, 1:1.5, 1:1, 1:0.5. The prepared tablets were evaluated for general appearance, content uniformity, hardness, friability, taste evaluation, mouth feel, in vitro disintegration time, and in vitro dissolution studies. Tablets with Precirol ATO-05 have shown good disintegrating features, also, the dispersion not showing any bitter taste, indicate the capability of Precirol ATO-05 used, both as taste masking agents. Almost more than 90 percent of drug was released from the formulation within 1 h. Further formulations were subjected to stability testing for 3 months at temperatures 25±5ºC/60±5%RH; 30±5ºC/65±5%RH and 40±5ºC/75±5%RH. Tablets have shown no appreciable changes with respect to taste, disintegration, and dissolution profiles.